Implementation of a Web-Based Information System: A Case Study of Intuisi Coffee, Central Aceh (Elkom: Jurnal Elektronika dan Komputer, 2025)
Intuisi Coffee, a café located in Blang Kolak, Central Aceh, still manages its ordering and transaction processes manually, which leads to inefficiencies in record-keeping, stock management, and report preparation. This study aims to implement a web-based information system to enhance the café's operational efficiency. The system was developed using the Waterfall method, utilizing XAMPP, PHP, and MySQL as the main technologies. System evaluation was conducted using the System Usability Scale (SUS) to assess usability in terms of effectiveness, efficiency, and user satisfaction. The evaluation resulted in a SUS score of 64.9, indicating a fairly good level of usability. The implementation of this system has proven to accelerate transaction processes, simplify data management, and support more structured decision-making.